The strange case of dr. jekyll and mr. hyde - Stevenson, Robert Louis (2023)
First published in 1886. The Strange Case of Dr. Jekyll and Mr. Hyde is a gothic novella. It tells the story of a London lawyer named Gabriel John Utterson. who investigates strange occurrences between his old friend Dr. Henry Jekyll and the evil Mr. Edward Hyde. The book explores the inner demons every human has to face. making this a classic tale of man versus self-exploration. Written in an engaging style that only Robert Louis Stevenson could create. this book is a must-read